Risk-Based Administrative Governance Model Through Compliance Management Integration in Mitigation of Audit Findings in Education Units - Amar Ma'rup Nahi Munkar (Innovative Pedagogy and Education Studies, 2026)
This study aims to develop and analyze a risk-based administrative governance model through the integration of compliance management in mitigating audit findings in education units. The research focus is directed at the relationship between administrative governance, risk management, and compliance management and their implications for the decline in audit findings. This study uses a mixed method approach with an explanatory sequential design, where quantitative data is collected through questionnaires analyzed using inferential statistical techniques, while qualitative data is obtained through in-depth interviews, observations, and documentation studies to strengthen and explain quantitative findings. The results of the study show that risk-based administrative governance integrated with compliance management has a significant influence on lowering audit findings. Educational units that systematically implement risk identification and mitigation and integrate compliance in administrative processes tend to have lower levels of administrative errors. In contrast, a procedural administrative approach without risk analysis has been shown to increase the potential for repetitive audit findings Integration between risk management and compliance has also been shown to improve the accountability and effectiveness of administrative management. The implications of this study show the importance of strengthening the risk-based administrative governance system as a preventive strategy in improving the quality of education management. The results of this study can be a reference for education unit managers and policy makers in formulating a governance model that is more adaptive, systematic, and prevention-oriented.